Control of vibration power input to semi-infinite anisotropic beam - Abd. Rahman, Roslan (Faculty of Mechanical Engineering, 2000)
The time averaged vibration power input to semi-infinite beam of anisotropic materials subjected to simultaneously acting bending force and moment excitations is presented. Fibre-reinforced composite materials of several types of ply and of various laminate arrangement were selected. The power input was minimized due to cancellation effect attributed to the coupling mobility between force and moment components. The cancellation effect frequency could be controlled by regulating the properties of the anisotropic materials.